Utopianism : A Very Short Introduction - Sargent, Lyman Tower, 1940- (Oxford, New York Oxford University Press, 2010)
There are many debates about utopia - What constitutes a utopia? Are utopias benign or dangerous? The idea of utopia has become commonplace in social and political thought, both negatively and positively. This Very Short Introduction explores utopianism, its history, and its role in modern debates
Include Illustration and Index
Keywords: Utopias